2022
DOI: 10.1021/acsnano.2c08436
|View full text |Cite
|
Sign up to set email alerts
|

Sn Dopants with Synergistic Oxygen Vacancies Boost CO2 Electroreduction on CuO Nanosheets to CO at Low Overpotential

Abstract: Using the electrochemical CO 2 reduction reaction (CO 2 RR) with Cu-based electrocatalysts to achieve carbonneutral cycles remains a significant challenge because of its low selectivity and poor stability. Modulating the surface electron distribution by defects engineering or doping can effectively improve CO 2 RR performance. Herein, we synthesize the electrocatalyst of V o -CuO(Sn) nanosheets containing oxygen vacancies and Sn dopants for application in CO 2 RR-to-CO. Density functional theory calculations c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 50 publications
(76 reference statements)
0
33
0
Order By: Relevance
“…S8 †), further proving that the Ni-N x active sites can accelerate the reaction kinetics of Ni/N-C catalysts in the CO 2 RR. 49,50 In addition, Fig. S9 Thus, the higher intrinsic activity of Ni/N-C-900 is attributed to its unique Ni-N x sites.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…S8 †), further proving that the Ni-N x active sites can accelerate the reaction kinetics of Ni/N-C catalysts in the CO 2 RR. 49,50 In addition, Fig. S9 Thus, the higher intrinsic activity of Ni/N-C-900 is attributed to its unique Ni-N x sites.…”
Section: Resultsmentioning
confidence: 95%
“…S8†), further proving that the Ni–N x active sites can accelerate the reaction kinetics of Ni/N–C catalysts in the CO 2 RR. 49,50…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2d, the EPR intensity of all the HBMs was enhanced compared with Bi 2 O 3 powders, especially for HBM‐600. Thus, we speculated that the lattice strain derived from the cotton template favored the formation of oxygen vacancies of Bi 2 O 3 during the pyrolysis of Bi‐Cotton [29,30] …”
Section: Resultsmentioning
confidence: 99%
“…Thus, we speculated that the lattice strain derived from the cotton template favored the formation of oxygen vacancies of Bi 2 O 3 during the pyrolysis of Bi-Cotton. [29,30] To investigate the catalytic performance of HBMs, we firstly evaluated the eCO 2 R performance on different materials as made in an H-cell. Before the electrochemical tests, high-purity CO 2 gas was firstly passed into 0.1 m KHCO 3 electrolyte at a constant flow rate of 20 sccm for at least 30 min until saturation.…”
Section: Resultsmentioning
confidence: 99%
“…Han and co-workers have developed Sn-doped CuO electrocatalysts for robust CO 2 reduction to CO due to the stabilization of Cu &+ . Through surface engineering, Sn-doped CuO nanosheets with oxygen vacancies were demonstrated to show high activity and selectivity toward CO . In contrast, Sun and co-workers reported that the combination of Sn doping and oxygen vacancies can synergistically boost CO 2 reduction to C 2 H 4 over Sn-doped CuO nanosheets .…”
Section: Introductionmentioning
confidence: 99%